= العُرف: دراسة أصولية اجتماعية al-'urf: dirasah usuliyah ijtima'yyah - Soualhi, Younes; Ghalia, Bouhedda (IIITالمعهد العالمي للفكر الإسلامي, 2015)
This study addresses the concept of custom as an influential factor in building and developing human societies. Using comparative-analytical research methods, it examines both revealed knowledge (Qur'an and Sunnah) of Muslim Usuli jurists and positivistic knowledge propagated by contemporary scholars of law and sociology in relation to the emergence and development of customs. It also aims at finding methodological instruments, and discovering the governing social laws necessary to develop societies both physically and spiritually.